2021
DOI: 10.1021/acsenergylett.1c00643
|View full text |Cite
|
Sign up to set email alerts
|

Inelastic Neutron Scattering Observation of Plasma-Promoted Nitrogen Reduction Intermediates on Ni/γ-Al2O3

Abstract: Plasma-assisted catalysis is an emerging technology for the atmospheric pressure and low bulk gas temperature synthesis of ammonia from molecular nitrogen and hydrogen. Direct evidence for plasma-induced surface reaction intermediates relevant to ammonia production, including surface hydrides and NH x (x = 1, 2, 3) species, has remained elusive. Here we report inelastic neutron scattering (INS) observations of alumina-supported Ni particles after treatment with N2 and H2 plasmas. INS experiments reveal the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 40 publications
6
41
0
Order By: Relevance
“…Figure b shows that H 2 plasma was able to break the NN triple bond of the adsorbed N 2 on the Ni surface, forming coordinated *NH 3 (ν as (NH 3 ): 3393 cm –1 ; ν s (NH 3 ): 3222 cm –1 ; δ as (NH 3 ): 1639 cm –1 ; δ as (NH 3 ) or δ as (NH 4 + ): 1550, 1525 cm –1 ). A small IR peak at 1403 cm –1 represents *NH species, which is one of the critical intermediates in the surface reactions of ammonia synthesis . Compared to the bare MCM-41, the metallic Ni sites, especially on the external surface of MCM-41, promoted the formation of surface *NH x ( x = 1 and 2) amide groups significantly, as indicated by the increased intensity of the characteristic IR peaks at 3120 cm –1 (for ν as (NH x )), 3019 cm –1 (for ν s (NH x )), and 1403 cm –1 (Ni–*NH x ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure b shows that H 2 plasma was able to break the NN triple bond of the adsorbed N 2 on the Ni surface, forming coordinated *NH 3 (ν as (NH 3 ): 3393 cm –1 ; ν s (NH 3 ): 3222 cm –1 ; δ as (NH 3 ): 1639 cm –1 ; δ as (NH 3 ) or δ as (NH 4 + ): 1550, 1525 cm –1 ). A small IR peak at 1403 cm –1 represents *NH species, which is one of the critical intermediates in the surface reactions of ammonia synthesis . Compared to the bare MCM-41, the metallic Ni sites, especially on the external surface of MCM-41, promoted the formation of surface *NH x ( x = 1 and 2) amide groups significantly, as indicated by the increased intensity of the characteristic IR peaks at 3120 cm –1 (for ν as (NH x )), 3019 cm –1 (for ν s (NH x )), and 1403 cm –1 (Ni–*NH x ).…”
Section: Resultsmentioning
confidence: 99%
“…A small IR peak at 1403 cm −1 represents *NH species, which is one of the critical intermediates in the surface reactions of ammonia synthesis. 55 Compared to the bare MCM-41, the metallic Ni sites, especially on the external surface of MCM-41, promoted the formation of surface *NH x (x = 1 and 2) amide groups significantly, as indicated by the increased intensity of the characteristic IR peaks at 3120 cm −1 (for ν as (NH x )), 3019 cm −1 (for ν s (NH x )), and 1403 cm −1 (Ni−*NH x ). Note that the IR peaks of NN stretching between 1900 and 2000 cm −1 are absent, which reveals that in the presence of H and H 2 radicals, *N 2 species could be rapidly dissociated and hydrogenated to form *NH x species on the catalyst surface, instead of forming adsorbed *N 2 H x species (which are the major intermediates in the electrochemical nitrogen reduction reactions 56,57 ).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In the context of ammonia synthesis, the formation of N, H, NH, NH 2 , and NH 3 in the gas phase ,, and their interactions with solid surfaces ,,, have been examined in plasma kinetic model analysis. The presence of NH x species in the gas-phase plasma or on catalyst surfaces in plasma has been demonstrated in experiments by using optical emission spectroscopy, X-ray photoelectron spectroscopy, and inelastic neutron scattering . Hwang and Mebel calculated rate constants for thermal NH 3 synthesis in the gas phase including intermediates such as NH, NH 2 , NNH, and N 2 H 2 ; however, according to their rate models, the concentrations of these intermediates in the gas phase are very low at the temperature used in our study, and therefore, they play an insignificant role in thermal reactions.…”
mentioning
confidence: 75%
“…The presence of NH x species in the gas-phase plasma or on catalyst surfaces in plasma has been demonstrated in experiments by using optical emission spectroscopy, 28 X-ray photoelectron spectroscopy, 14 and inelastic neutron scattering. 29 Hwang and Mebel 30 calculated rate constants for thermal NH 3 synthesis in the gas phase including intermediates such as NH, NH 2 , NNH, and N 2 H 2 ; however, according to their rate models, the concentrations of these intermediates in the gas phase are very low at the temperature used in our study, and therefore, they play an insignificant role in thermal reactions. Winter et al 31 identified surface reaction intermediates such as N 2 H y in plasma catalytic ammonia synthesis, although these species were not separately identified and quantified.…”
mentioning
confidence: 81%
“…Stere et al developed an in situ DRIFTS coupled with mass spectrometry (MS) instrument to simultaneously investigate the surface species and formation of products in hydrocarbon selective catalytic reduction of nitrogen oxides (NO x ) over a silverbased catalyst with a helium plasma jet and identified the importance of isocyanate species being the active intermediates. 26 X-ray absorption spectroscopy 30 and inelastic neutron scattering 31 have also been used to reveal the role of plasmas in the hybrid NTP catalytic oxidation of methane and plasmapromoted nitrogen reduction, respectively.…”
Section: Introductionmentioning
confidence: 99%